Effects of matched intermittent and continuous exercise on changes of cardiac biomarkers in endurance runners - Li, F.; Nie, J.; Zhang, H.; Fu, F.; Yi, L.; Hopkins, W.; Liu, Y.; Lu, Y. (Frontiers in Physiology, 2020)
Purpose: Endurance runners training with high-intensity intermittent exercise might experience damage to cardiac muscle. We have therefore compared changes of cardiac biomarkers after workload-matched intermittent and continuous exercise.